Synthesis and Characterization of Titanium Supported on High Order Nanoporous Silica and Application for Direct Oxidation of Benzene to Phenol - Alireza Badiei; Javad Gholami; Yeganeh Khaniani (E-Journal of Chemistry)
Direct oxidation of benzene to phenol in liquid phase by H2O2 peroxide was examined over Ti/ LUS-1 catalyst in methanol and acetic acid as solvents. The maximum yield and selectivity of the phenol produced was obtained in the presence of acetic acid. It can be attributed to the stabilization of H2O2 as peroxy acetic acid species in the radical mechanism for this reaction. Acetic acid interacts with hydrogen peroxide over Ti/LUS-1 and produces acetoxy radicals.